Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan Remaja Putri tentang Penanganan Dismenore dengan Kompres Hangat di SMA Katolik Santo Augustinus Kediri - Taviyanda, Dian; Selvia David Richard; Rimawati (Jurnal Kesehatan, 2022)
Menstruation is a process when the uterus is cleaned, so that it will be ready for the next reproductive cycle. One of the menstruation disorders is dysmenorrhea. Dysmenorrhea is a lower-sectional abdominal pain that appears before or during menstruation. There are still many teenage girls who overcome dysmenorrhea by using analgetic, and have never received information about the treatment of dysmenorrhea. The purpose of this study is to know whether health education affects the level of knowledge of teenage girl about treating dysmenorrhea using warm compress at St. Augustinus Catholic High School Kediri. The design of this study was pre-experimental study using one group pre-post test design. The population of this study were third year teenage girls at senior high school (class XII) who experienced dysmenorrhea during menstruation at St. Augustinus Catholic High School Kediri. The sample of this study were 30 respondents, using purposive sampling techniques. The independent variable of this study is health education and the dependent variable is the level of knowledge. The data collection was carried out using questionnaires. Data then analyzed using Wilcoxon test with significant α<0.05. The results showed that the level of knowledge about treating dysmenorrhea using warm compress increased after health education, as evidenced by the results of the wilcoxon statistical test where p=0.000. In conclusion, there is an influence of health education on the level of knowledge of teenage girl about treating  dysmenorrhea using compress at St. Augustinus Catholic High School Kediri.